Arterial spin labeling image findings in the acute phase in paediatric patients with acute encephalopathy with biphasic seizures and late reduced diffusion - Go Kawano; Kentaro Tokutomi; Yoshitomo Kikuchi; Kensuke Sakata; Hirotaka Sakaguchi; Takaoki Yokochi; Yukihiro Akita; Toyojiro Matsuishi; Toyojiro Matsuishi; Toyojiro Matsuishi (Frontiers in Neuroscience, 2023)
IntroductionDiagnosing acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) after the first seizure (early seizure/seizures, ES/ESs) is challenging because a reduced apparent diffusion coefficient (ADC) in the cortical or subcortical white matter, often described as having a “bright-tree appearance (BTA),” is usually not observed until secondary seizures (late seizures, LSs) occur. Previous studies have reported hypoperfusion on arterial spin labeling (ASL) within 24 h after ES/ESs in patients with AESD and hyperperfusion within 24 h after LS onset. This study aimed to investigate cerebral blood flow in the hyperacute phase (between ES/ESs and LSs) using ASL in patients with AESD.MethodsEight ASL images were acquired in six patients with AESD admitted to our hospital from October 2021 to October 2022. ASL findings in the hyperacute phase were investigated and video-electroencephalogram findings obtained around ASL image acquisition in the hyperacute phase were evaluated.ResultsFour ASL images were obtained for three patients before LS onset, with three images showing hyperperfusion areas and one image showing hypoperfusion areas. These hyperperfuion regions coincided with BTA on subsequent images of these patients.In one patient, the first ASL image was obtained in the late hyperacute phase and revealed hyperperfusion areas with a slightly abnormal change on diffusion-weighted image (DWI), which were not accompanied by ADC abnormalities. The second ASL image obtained 51 h after the first ASL, and before LS onset revealed more prominent hyperperfusion areas than the first ASL image, which were accompanied by BTA. In another patient, the ASL image obtained 82 h after ES revealed hyperperfusion areas without abnormal change on DWI or ADC.ConclusionThis study revealed that two patients exhibited hyperperfusion regions and another patient exhibited hypoperfusion regions among three patients who underwent ASL imaging during the period from 24 h after ES/ESs to LSs in patients with LSs or cooling initiation in patients without LSs due to early anaesthesia induction (late hyperacute phase). Further prospective studies on cerebral blood flow are required to explore the relationship among the timing of image acquisition, the presence of electrographic seizures, and ASL findings in patients with AESD.